1989
DOI: 10.1056/nejm198906083202302
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Controlled Trial of Very Early Prophylactic Ligation of the Ductus Arteriosus in Babies Who Weighed 1000 g or Less at Birth

Abstract: We speculated that prophylactic ligation of the ductus arteriosus would reduce mortality and morbidity in very-low-birth-weight infants. To test this hypothesis, we randomly assigned 84 babies who weighed 1000 g or less at birth and required supplemental oxygen either to receive standard treatment (n = 44) or to undergo prophylactic surgical ligation of the ductus arteriosus on the day of birth (n = 40). The ductus was ligated in babies in the control group only if the shunt was hemodynamically important. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
127
0
8

Year Published

1995
1995
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(139 citation statements)
references
References 18 publications
2
127
0
8
Order By: Relevance
“…36 Of 25 studies reporting the combined outcome of death or BPD, only one showed a reduction. 78 A single trial of prophylactic ligation described a decrease in NEC, 64 and one trial of ibuprofen prophylaxis found more NEC, 87 but most found no effect. IVH rates were lower in 3 trials of prophylactic indomethacin, 91,96,98 2 trials reported lower rates of IVH>grade 2, 100,106 and 30 found no effect.…”
Section: Findings From Individual Randomized-controlled Trialsmentioning
confidence: 99%
See 3 more Smart Citations
“…36 Of 25 studies reporting the combined outcome of death or BPD, only one showed a reduction. 78 A single trial of prophylactic ligation described a decrease in NEC, 64 and one trial of ibuprofen prophylaxis found more NEC, 87 but most found no effect. IVH rates were lower in 3 trials of prophylactic indomethacin, 91,96,98 2 trials reported lower rates of IVH>grade 2, 100,106 and 30 found no effect.…”
Section: Findings From Individual Randomized-controlled Trialsmentioning
confidence: 99%
“…29 Analysis of data from the Trial of Indomethacin Prophylaxis in Preterms trial suggested that ductal ligation compared with medical therapy alone is associated with more neurosensory impairment, BPD, and severe ROP. 34 Re-examining data from a randomized trial of prophylactic ligation, 64 Clyman et al 36 found that ligation increased the likelihood of requiring oxygen at 36 weeks PMA. In a retrospective regression analysis of factors associated with morbidity in infants treated for PDA, Chorne et al 35 found that chronic lung disease (oxygen use at 36 weeks PMA) is associated with ductal ligation, but not with use of >3 indomethacin doses, persistent PDA after indomethacin prophylaxis, or symptomatic PDA.…”
Section: Findings From Individual Randomized-controlled Trialsmentioning
confidence: 99%
See 2 more Smart Citations
“…54 In a controlled and randomized trial with premature infants with birth weights less than or equal to 1,000 g, Cassady et al observed that early surgical ligature of the ductus arteriosus reduces the chance of NEC developing. 55 From the eighties onwards indomethacin began to be used prophylactically for closing ductus arteriosus and prevention of intracranial hemorrhage. The research that followed showed an effective action in reducing these situations although side effects such as reduced splenic blood flow put a check on the universal recommendation for their usage.…”
Section: Early Closing Of Patent Ductus Arteriosusmentioning
confidence: 99%